Impact of COVID-19 Pandemic on Road and Bridge Projects under Road Division Pokhara - Subedi, Kiran; Baral, Nirmal (Himalayan Journal of Applied Science and Engineering, 2024)
COVID-19 is a global pandemic that has caused social disruption and altered the global economic perspective. The construction sector plays an essential role in the worldwide economy, drawing upon a diverse array of resources within regional economies. Since the COVID-19 outburst in Nepal, it has been a really difficult task for the construction sector to initiate a project or to continue running at a normal pace. The objective of this research was to determine the impact of COVID-19 on the road and bridge project under the road division Pokhara. About 52 respondents comprised contractors and client/consulting agencies at different structure questionnaires compatible with the requirement of the study were recorded. As a result, the eight most important factors were ranked based on the severity of the effect and prioritization of multiple factors on the project due to the pandemic. Obtained responses from consultant and contractor representatives, it was found that the factors beyond the control of projects, transportation shutdown were ranked first followed by the shortage of labor under manpower factor and others. This paper observes the actual severity of the various factors regarding construction projects due to the corona virus and will also lead to better management in upcoming pandemics. The results of this study establish the groundwork for future researchers and practitioners by offering suggestions for how to prioritize and re-organize work plans, workplace management, and strategies for unforeseen circumstances.